Efficient Amplification in Soai's Asymmetric Autocatalysis by a Transient Stereodynamic Catalyst - Trapp, Oliver (Frontiers in Chemistry, 2020)
Mechanisms leading to a molecular evolution and the formation of homochirality in nature are interconnected and a key to the underlying principles that led to the emergence of life. So far proposed mechanisms leading to a non-linear reaction behavior are based mainly on the formation of homochiral and heterochiral dimers. Since homochiral and heterochiral dimers are diastereomers of each other, the minor enantiomer is shifted out of equilibrium with the major enantiomer by dimer formation and thus a reaction or catalysis can be dominated by the remaining molecules of the major enantiomer. In this article a mechanism is shown that leads to homochirality by the formation of a highly catalytically active transient intermediate in a stereodynamically controlled reaction. This is demonstrated by Soai's asymmetric autocatalysis, in which aldehydes are transformed into the corresponding alcohols by addition of dialkylzinc reagents. The mechanism of chirogenesis proposed here shows that an apparently inefficient reaction is the best prerequisite for a selection mechanism. In addition, stereodynamic control offers the advantage that the minor diastereomeric intermediate can be interconverted into the major diastereomer and thus be stereoeconomically efficient. This is supported by computer simulation of reaction kinetics.